Reducing Postoperative Opioids in Pediatric Orthopaedics: An Updated Tiered Prescription Guideline with a “Tier 0” - Mikaela H. Sullivan, MD; Courtney E. Baker, MD; Daniel S. Ubl, MPH; Elizabeth B. Habermann, MPH, PhD; A. Noelle Larson, MD; Todd A. Milbrandt, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: There is growing data on strategies to reduce opioid prescriptions in pediatric orthopaedics. Our institution implemented tiered guidelines for opioid discharge prescriptions in 2018 to standardize prescribing patterns across our entire pediatric orthopaedics practice. In 2022, we updated the tiered system with a goal to further minimize the quantity of opioids prescribed and eliminate opioids altogether for certain procedures. The aim of this project was to evaluate the effects of the updated tiered guidelines for discharge opioid prescribing following common pediatric orthopaedic procedures. Methods: A quality improvement project was conducted at a single academic institution. Guidelines for discharge opioid prescriptions were updated in January 2022 and established 5 tiers of increasing invasiveness for 28 procedures. The updated guidelines included a “Tier 0” which provided no opioids, reorganized surgical tiers based on prior data, and decreased the doses recommended for tiers. Opioid prescriptions were reported as oral morphine equivalents (OMEs). Univariate tests were performed to assess statistically significant differences before and after implementation of updated guideline eras, comparing 2020–2021 and 2022. Results: Overall, 747 patients (2020–2021, n ​= ​500; 2022, n ​= ​247) were included. The proportion of patients receiving discharge opioid prescriptions decreased from 89.8% to 80.6% (P ​< ​0.05), between 2020 and 2021 and 2022. This resulted in decreased overall OME prescribed (median 75 vs 45, P ​< ​0.05) and OME prescribed in those >10 years (135 vs 113, P ​< ​0.05) while 30-day refill rates (9.4% vs 6.1%), and OME per kilogram in those <11 years of age (median 0.9 vs 0.8) remained unchanged (both P ​> ​0.05). Discharge prescriptions falling within overall guidelines increased after guideline implementation (83.3% vs 85.4%), though this was not statistically significant and guideline adherence was low among Tier 0 ​at 31%. Conclusions: Including “Tier 0” of procedures receiving no opioid prescriptions, reorganizing procedures within tiers, and decreasing the recommended doses to an already strict tiered guideline for discharge opioid prescriptions significantly decreased the quantity of opioids prescribed. We noted continued excellent overall adherence and, importantly, no overall increase in refills, with areas for improvement in Tier 0. Quality improvement projects can continue to reduce the amount of opioids prescribed following pediatric orthopaedic procedures. Key Concepts: (1) Updated tiered guidelines, including a “Tier 0” for discharge opioid prescriptions following pediatric orthopaedic procedures were effective in reducing the quantity of opioids provided at discharge. (2) A continued high adherence rate was observed with the updated guidelines, though areas for improvement include adherence to no opioids in Tier 0. (3) Refill rates remained similar after implementation of the updated guidelines. (4) The study results suggest opportunities for continued improvement projects to reduce the number of unnecessary opioids prescribed to pediatric orthopaedic patients. Level of Evidence: III.